Intensity‐specific effect of physical activity on urinary levels of 8‐hydroxydeoxyguanosine in middle‐aged Japanese. Issue 11 (November 2016) - Hara, Megumi; Nishida, Yuichiro; Shimanoe, Chisato; Otsuka, Yasuko; Nanri, Hinako; Yasukata, Jun; Miyoshi, Nobuyuki; Yamada, Yosuke; Horita, Mikako; Kawai, Kazuaki; Li, Yun‐Shan; Kasai, Jun; et al.
Abstract : Physical activity (PA) is recommended to both promote and maintain health and prevent cancer by improving the body's DNA repair system, which is considered a mechanism of cancer prevention. However, associations between PA and urinary levels of 8‐hydroxydeoxyguanosine (8‐OH‐dG), which reflects DNA damage, are unclear. This cross‐sectional study included 2370 men and 4052 women aged 45–74 years enrolled between 2010 and 2012. Habitual PA was assessed by single‐axis accelerometer and urinary 8‐OH‐dG levels by automated HPLC. Multiple linear regression analysis was used to examine the relationship between log‐transformed urinary 8‐OH‐dG and total PA (TPA) and PA of moderate/vigorous intensity (MVPA; ≥3 metabolic equivalents), with adjustment for age, body mass index, energy intake, alcohol consumption, smoking status, daily coffee drinking, menopause status (in women), and TPA (for MVPA). On multivariate adjustment, urinary 8‐OH‐dG levels were inversely correlated with TPA (β = −0.020, P  < 0.01) in women, and this correlation was not changed by PA intensity. Conversely, urinary 8‐OH‐dG levels were inversely correlated with MVPA (β = −0.022, P  < 0.05) in men, although the correlation with TPA was non‐significant. This inverse correlation was clearer in current smokers than in never or former smokers, although the interaction between smoking status and MVPA on urinary 8‐OH‐dG levels was non‐significant. In conclusion, greater TPA in women and greater MVPA in men were correlated with reduction in urinary 8‐OH‐dG, suggesting sex‐specific effects of MVPA and TPA on protection from oxidative DNA damage. Increasing PA may mediate reduction in oxidative stress. Abstract : Increasing physical activity may mediate reduction in oxidative stress.